ANALISA PENGARUH PANJANG GELOMBANG SUMBER CAHAYA PENGINDUKSI FLUORESENSI TERHADAP FLUORESENSI KLOROFIL PADA DAUN BAYAM YANG DIPENGARUHI VARIASI SINAR MATAHARI - Fitria Asriani; Minarni ' (Komunikasi Fisika Indonesia, 2015)
Chlorophyll fluorescence imaging and spectroscopy can be used to detect early abnormalities on plants, which are caused by plant diseases, harsh environments, and intentional treatments. Development in chlorophyll imaging and spectroscopy which is economical, low cost, and portable are needed in attempts to explore fluorescence spectrum as markers for diseases and environmental stresses on plants. In this research, a fluorescence imaging system was built using LEDs with three variations in wavelengths i.e. 450 nm; 525 nm; and 680 nm, and a 3 Mega Pixel CMOS camera. The LED light was used as an excitation beam to induce chlorophyll fluorescence of spinach leaves. Relation between the LED wavelengths and the fluorescence intensities of the spinach leaves were investigated. The samples were Spinach leaves from Amaranthus tricolor Spinach plants grown under two variations of sunlight intensities. Two variations of the intensities were about 90% using plastic as the cover and 40% using plastic plus paranet. Relation between the sunlight intensity and fluorescence intensity was also investigated. The fluorescence intensity of the leaves were measured from RGB plot using Image-J software. The research results show that fluorescence intensity of the samples without paranet were higher than those using paranet. This is possibly caused by chlorophyll contents which is higher on plants without paranet. The excitation wavelength that showed the highest different fluorescence intensity was 680 nm, which showed 6,3% the difference in fluorescence intensity using and without paranet while for other excitation wavelength were 0,4% and 1,7% for 450 nm and 525 nm respectively.